Bahasa inggris - Mauliza, Ulvi; Wintah; Musnadi, Jun; Rismawati, Rismawati; Saputra, Firman Firdauz (Pena Medika : Jurnal Kesehatan, 2024)
Industry development in Indonesia has experienced a significant increase in recent years, one of which is the growth of the rubber processing sector. One of the business conditions that has the potential to endanger lung health is the rubber processing production sector. The purpose of this study was to identify variables related to complaints from employees in the production division of PTPN Regional IV Kebun Bandar Betsy. This study used a cross-sectional study design, and quantitative research through analytical investigation. All employees in the rubber processing production division total 73 rubber processing factories became the study population, the total sampling procedure was used to select a sample of 73 respondents from December 1 to December 31, 2023. Research Analysis Using the Chi-Square test, data analysis was carried out univariately and bivariately. The results of the statistical test showed that the p-value (0.023), there was a relationship between work experience and complaints of respiratory disorders, the p-value (0.011) there was a relationship between smoking habits and complaints of respiratory disorders, the p-value (0.006) between the use of personal protective equipment and complaints of respiratory disorders. Based on the results of the study, employees of the rubber processing production of PT. reported respiratory disorders related to length of service, smoking habits, and use of personal protective equipment. Therefore, the recommendation is to provide training on occupational health hazards in the rubber processing industry, as well as safe techniques and procedures to avoid health risks, including the correct use of PPE.